Hi there!
Let's solve this equation step by step!
6f + 9g = 3g + f
To solve for f, we need to bring all the terms in the equation with an f in it to the left, and all the other terms (with a g) to the right.
First subtract f from both sides.
5f + 9g = 3g
Now subtract 9g from both sides.
5f = -6g
And finally divide both sides by 5.
f = (-6/5)g
Hence, your answer;
~ Hope this helps you!
We can use the formula y2-y1/x2-x1 to find our answer. So, we have : t-16/5-2 = -3. We simplify that to t-16/3 = -3. We can then multiply both sides by 3 to get t-16 = -9. Then we can add 16 to both sides to get t = 7.
Answer:
295.2
Step-by-step explanation:
Answer: 30 servers
5+2 = 7
42/7 = 6 sets of employees
5*6 = 30 servers
Step-by-step explanation:
5+2 = 7
42/7 = 6 sets of employees
5*6 = 30 servers
Answer:
Step-by-step explanation:
Angle C and angle with 120 degrees measure are alternate and their measurement is equal so C = 120
angle C and angle B are supplementary and so their sum is equal to 180
B = 180 - 120
B = 60
angle D and angle B are also alternate so their measure is also equal to each other therefore
D = 60